Association of personalised care plans with monitoring and control of clinical outcomes, prescription of medication and utilisation of primary care services in patients with type 2 diabetes: an observational real-world study. (2nd January 2022) - Mikkola, Ilona; Morgan, Simon; Winell, Klas; Jokelainen, Jari; Frittitta, Lucia; Heikkala, Eveliina; Hagnäs, Maria
Abstract: Objective: To study the association of personalised care plans with monitoring and controlling clinical outcomes, prescription of cardiovascular and antihyperglycaemic medication and utilisation of primary care services in patients with type 2 diabetes (T2D). Patients: Primary care T2D outpatients from the Rovaniemi Health Centre. Setting: The municipal health centre, Rovaniemi, Finland. Design: A cross-sectional, observational, retrospective register-based study. The patients were divided into three groups: 'no care plan entries' (usual care); '1–2 care plan entries'; and '3 or more care plan entries'. Main outcome measures: Monitoring of clinical and biochemical measures, achievement of treatment targets, prescription of cardiovascular and antihyperglycemic medication, and use of primary care services. Results: A total of 5104 patients with T2D (mean age 65.5 years (SD 12.4)), of which 67% had at least one care plan entry. Compared to usual care, the establishment of a care plan (either care plan group) was associated with better monitoring of glycosylated haemoglobin A1c, low-density-lipoprotein cholesterol, systolic blood pressure (sBP), and renal function, and there was more frequent prescription of all cardiovascular and antihyperglycemic medication. Patients in either care plan group were more likely to achieve sBP target ( p < 0.05). Patients without a care plan had more unplanned primary care physician contacts compared to patients in care plan groups ( p < 0.001). Conclusion: Establishment of a care plan is associated with more intensive and focussed care of patients with T2D. The appropriate use of primary care resources is essential and personalised care plans may contribute to the treatment of patients with T2D. Key Points: Care planning aims to empower patients with type 2 diabetes. This study demonstrates that personalised care planning is associated with more frequent monitoring for clinical outcomes, more frequent prescription of cardiovascular and antihyperglycemic medication and more frequent utilisation of planned diabetes consultations when compared to usual care.